VIP1 and Its Homologs Are Not Required for Agrobacterium-Mediated Transformation, but Play a Role in Botrytis and Salt Stress Responses - Lapham, Rachelle; Lee, Lan-Ying; Tsugama, Daisuke; Lee, Sanghun; Mengiste, Tesfaye; Gelvin, Stanton B. (Frontiers in Plant Science, 2018)
The bZIP transcription factor VIP1 interacts with the Agrobacterium virulence protein VirE2, but the role of VIP1 in Agrobacterium-mediated transformation remains controversial. Previously tested vip1-1 mutant plants produce a truncated protein containing the crucial bZIP DNA-binding domain. We generated the CRISPR/Cas mutant vip1-2 that lacks this domain. The transformation susceptibility of vip1-2 and wild-type plants is similar. Because of potential functional redundancy among VIP1 homologs, we tested transgenic lines expressing VIP1 fused to a SRDX repression domain. All VIP1-SRDX transgenic lines showed wild-type levels of transformation, indicating that neither VIP1 nor its homologs are required for Agrobacterium-mediated transformation. Because VIP1 is involved in innate immune response signaling, we tested the susceptibility of vip1 mutant and VIP1-SRDX plants to Pseudomonas syringae and Botrytis cinerea. vip1 mutant and VIP1-SRDX plants show increased susceptibility to B. cinerea but not P. syringae infection, suggesting a role for VIP1 in B. cinerea, but not P. syringae, defense signaling. B. cinerea susceptibility is dependent on abscisic acid (ABA) which is also important for abiotic stress responses. The germination of vip1 mutant and VIP1-SRDX seeds is sensitive to exogenous ABA, suggesting a role for VIP1 in response to ABA. vip1 mutant and VIP1-SRDX plants show increased tolerance to growth in salt, indicating a role for VIP1 in response to salt stress.